Synergistic Effect of Flavonoid-rich Ethanolic Extract of Coccinia indica and Hesperidin in Diabetes Induced Neuropathic Rat Model - Gurung, Pravash; Nanjundan, Prem Kumar; Chhetri, Royan; Chettri, Samuel; Gangadhar, Karthik (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Degeneration of neuronal function and diminished sensation characterize diabetic neuropathy, the foremost prevalent complication connected with diabetes mellitus. This research focuses on investigating the combined impact of flavonoid rich ethanolic extract of Coccinia indica extract (CIE) and hesperidin in diabetes induced neuropathy. Male sprague dawley rats were instigated with diabetic neuropathy (DN), following 14 days of high fat diet treatment along with streptozotocin (35 mg/kg, i.p), then the animals were maintained for 4 weeks to allow the development of DN. In accordance to the previous research identifying increased lipid peroxidation and reduced enzymatic antioxidants (superoxide dismutase, catalase, and reduced glutathione) as hallmark indicators of diabetic neuropathy (DN), our study demonstrated a similar biochemical profile. Treatment with CIE (200 mg/kg) alone and in combination with hesperidin at doses (25, 50 mg/kg), orally were conducted for eight weeks, which produced substantial reduction in blood sugar and restored antioxidant levels. Models for neurological pain (Eddy’s hot plate and Tail immersion) were utilized to assess the levels of antinociception. Post third week, the combined therapy of CIE and hesperidin exhibited significant (p<0.001) antinociception due to their ability to improve the insulin sensitivity (Increase in glucose tolerance) when compared with metformin. As CIE, hesperidin, and metformin are all known to activate AMP-activated protein kinase (AMPK), which subsequently leads to the inhibition of nuclear factor-kappa B (NF-κB) and other pertinent signaling pathways. This cascade ultimately results in the suppression of gluconeogenesis, inflammatory cytokines while enhancing insulin sensitivity and elevating antioxidant levels. This signifies that combination therapy with CIE+hesperidin is equivalent to metformin in delaying the progression of diabetes induced neuropathy. Histological examinations confirmed the absence of sciatic nerve damage. Combined therapy of CIE along with hesperidin yielded notable depletion in blood sugar concentration and prevented further development of diabetic neuropathy.